2020
DOI: 10.1017/dmp.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Natural History of Category 4 Tropical Cyclones: The Puerto Rico Trauma Hospital Experience after Hurricane Maria

Abstract: Objectives: The hazardous environmental conditions hurricanes create might increase injury incidence almost 7 times. Therefore, a cohort study was performed at the Puerto Rico Trauma Hospital to compare morbidity and mortality patterns of patients after Hurricane Maria with a control period. Methods: Admissions from September 20, 2017, through January 20, 2018, constituted the post-Maria period (473 patients); the corresponding months of the previous year comprised the pre-Maria period (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…The median age of injured patients increased from 40 to 49. Compared to our findings, studies in the past have shown that during periods of natural disasters and forced isolation (e.g., hurricanes, earthquakes, lockdowns), the population who presents to the hospital seeking care tends to be older (Comelli et al 2020;Ramos-Meléndez et al 2020).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The median age of injured patients increased from 40 to 49. Compared to our findings, studies in the past have shown that during periods of natural disasters and forced isolation (e.g., hurricanes, earthquakes, lockdowns), the population who presents to the hospital seeking care tends to be older (Comelli et al 2020;Ramos-Meléndez et al 2020).…”
Section: Discussioncontrasting
confidence: 86%
“…Along with assaults, falls were the predominant mechanism during the first month of the lockdown. According to the literature, it is among the top mechanisms that increase in frequency in the aftermath of a natural disaster (Ramos-Meléndez et al 2020). While this is not a natural disaster per se, it led to house confinement usually seen during and after natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, more visits after the storms were among patients with a primary diagnosis of injuries to the head, wrist and hand, ankle and foot, knee and lower leg, abdomen/lower back/spine/pelvis, neck, thorax, and elbow/forearm (Figure 1). This finding is consistent with prior studies, 17,20,24,[26][27][28][29][30] and is possibly because residents devoted considerable time attending to their damaged homes between storms and engaged in recovery activities known to produce injuries and health conditions in the aftermath of the hurricanes. 17,28,48…”
Section: Ed Visitssupporting
confidence: 91%
“…Substantial evidence shows the effects of power outages on healthcare delivery, home healthcare services, the public health infrastructure, and adverse health outcomes. [8][9][10][11][12][13] The effects of hurricanes on the increased utilization of EDs in New York, [14][15][16][17][18][19] New Jersey, [20][21][22] and Texas 23 ; across 9 U.S. states, 24 among Caribbean islands, [25][26][27][28][29][30] and the impact of a category 5 tropical cyclone on disaster related wounds, 31 have been recently investigated. The hurricane studies attributed the increased ED visits to disrupted access to care for a range of chronic diseases and conditions, including cardiovascular disease, diabetes, cancer, chronic obstructive pulmonary disease (including ventilator dependence), renal disease, dementia, and mental disorders; disaster-related conditions (such as hypothermia or environmental exposures); carbon monoxide-related accidents; and a lack of prescription refills.…”
Section: Introductionmentioning
confidence: 99%
“…The elderly population is more vulnerable to hurricanes’ direct and indirect impacts, as evident from an increase in the number of patients in the age group 40–64 following Hurricane Maria in Puerto Rico [ 39 ]. Following Hurricane Sandy, the proportion of visits for dialysis, respiratory issues, social and syncope visits was significantly higher for geriatric patients as compared to younger patients [ 40 ].…”
Section: Health Impacts Of Hurricane—a Reviewmentioning
confidence: 99%